60.9k views
3 votes
Combine the radicals. 3√5-8√5+2√5

User Annette
by
5.5k points

1 Answer

6 votes

Answer:
-3√(5)

-3 times the square root of 5

=============================================

Step-by-step explanation:

Let
x = √(5)

Replace all the root 5 terms with x and we go from


3√(5)-8√(5)+2√(5)

to


3x-8x+2x

From here, combine like terms to get


3x-8x+2x = -5x+2x = -3x

and the last thing to do is replace the x with sqrt(5)


-3x = -3√(5)

Meaning that,


3x-8x+2x = -3x


3√(5)-8√(5)+2√(5) = -3√(5)

User Gebezs
by
6.6k points